CLINICAL AND IMMUNOBIOCHEMICAL PREDICTORS IN THE DIAGNOSIS OF BRONCHIAL ASTHMA IN COMORBIDITY WITH TYPE 2 DIABETES MELLITUS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The aim of this study was to perform a comprehensive evaluation of clinical, laboratory, and immunobiochemical markers in patients with bronchial asthma (BA) combined with type 2 diabetes mellitus (T2DM). A comparative analysis of clinical manifestations, carbohydrate metabolism parameters, hemostatic system indices, and antioxidant defense was carried out. It was found that superoxide dismutase (SOD) activity in patients with comorbid pathology decreased to 1001.7 ± 75.4 pg/mL, which was 1.5 times lower than in the group with isolated bronchial asthma (1201.8 ± 68.2 pg/mL) (p < 0.05), indicating pronounced oxidative stress. At the same time, a significant increase in MMP-9 levels was observed: in BA patients it was 120.7 ± 2.25 ng/mL, while in patients with BA combined with T2DM it increased to 175.3 ± 3.23 ng/mL, exceeding control values (31.5 ± 1.23 ng/mL) by more than 5 times and those of isolated asthma by 1.45 times (p < 0.05). These findings indicate an important role of inflammatory and tissue remodeling processes in the pathogenesis of comorbid conditions. The obtained data confirm that metabolic and immunobiochemical alterations significantly contribute to the development of combined BA and T2DM and may be useful for improving early diagnosis and prognostic assessment.
Keywords: bronchial asthma, type 2 diabetes mellitus, MMP-9, immunobiochemical markers, superoxide dismutase, oxidative stress, diagnostics.